Genomic Features for Desiccation Tolerance and Sugar Biosynthesis in the Extremophile Gloeocapsopsis sp. UTEX B3054 - Urrejola, Catalina; Alcorta, Jaime; Salas, Loreto; Vásquez, Mónica; Polz, Martin F.; Vicuña, Rafael; Díez, Beatriz (Frontiers in Microbiology, 2019)
For tolerating extreme desiccation, cyanobacteria are known to produce both compatible solutes at intracellular level and a copious amount of exopolysaccharides as a protective coat. However, these molecules make cyanobacterial cells refractory to a broad spectrum of cell disruption methods, hindering genome sequencing and molecular studies. In fact, few genomes are already available from cyanobacteria from extremely desiccated environments such as deserts. In this work, we report the 5.4 Mbp draft genome (with 100% of completeness in 105 contigs) of Gloeocapsopsis sp. UTEX B3054 (subsection I; Order Chroococcales), a cultivable sugar-rich and hardly breakable hypolithic cyanobacterium from the Atacama Desert. Our in silico analyses focused on genomic features related to sugar-biosynthesis and adaptation to dryness. Among other findings, screening of Gloeocapsopsis genome revealed a unique genetic potential related to the biosynthesis and regulation of compatible solutes and polysaccharides. For instance, our findings showed for the first time a novel genomic arrangement exclusive of Chroococcaceae cyanobacteria associated with the recycling of trehalose, a compatible solute involved in desiccation tolerance. Additionally, we performed a comparative genome survey and analyses to entirely predict the highly diverse pool of glycosyltransferases enzymes, key players in polysaccharide biosynthesis and the formation of a protective coat to dryness. We expect that this work will set the fundamental genomic framework for further research on microbial tolerance to desiccation and to a wide range of other extreme environmental conditions. The study of microorganisms like Gloeocapsopsis sp. UTEX B3054 will contribute to expand our limited understanding regarding water optimization and molecular mechanisms allowing extremophiles to thrive in xeric environments such as the Atacama Desert.